Crystal structure of bis[(1,3-bis(4-pyridinium)propane)]- [β-hexacosaoxooctamolybdate(VI)], (C13H16N2)2[Mo8O26] - Wang C.-C. (Zeitschrift für Kristallographie - New Crystal Structures, 2006)
C26H32Mo8N4O26, monoclinic, P121/c1 (no. 14), a = 10.589(2) Å, b = 10.007(2) Å, c = 19.662(4) Å, β = 100.85(3)°, V = 2046.2 Å3, Z = 2, Rgt(F) = 0.023, wRref(F2) = 0.056, T = 293 K.